Ischemic Colitis in Sickle Cell Disease: A Case Report of a Diagnostic Challenge. (24th January 2018) - Geary, Kyle; Kibrit, Jacob
Abstract : Microvascular occlusion serves as the underlying mechanism for the multitude of clinical manifestations of sickle cell disease, one of the most prevalent hemoglobinopathies worldwide. Recurrent painful episodes are the hallmark of this condition. Abdominal pain attributed to an acute painful episode can be indistinguishable from a separate and/or more serious intra-abdominal disease process, representing a significant diagnostic dilemma for clinicians. Here we present a rare case of ischemic colitis due to vascular occlusion in a 28-year-old man with sickle cell disease.